Extracting flow curves from nano-sized metal layers in thin film systems. (15th March 2017) - Kozic, D.; Maier-Kiener, V.; Konetschnik, R.; Gänser, H.-P.; Antretter, T.; Brunner, R.; Kiener, D.
Abstract: In this work the plastic deformation behavior of nanocrystalline 500 nm thick tungsten and copper films deposited on a silicon substrate is investigated. Nanoindentation experiments utilizing a spherical tip are used to determine the mechanical response of the film stacks. The data is used as input for an inverse optimization routine coupled to finite element simulations in order to determine the flow curves of the individual materials. We elaborate on how locally resolved residual stresses, microstructure, and external dimensions determine and influence the flow behavior and compare the results to the corresponding bulk materials. Graphical abstract: